Geometric Optimization of a Step Bearing for a Hydrodynamically Levitated Centrifugal Blood Pump for the Reduction of Hemolysis. Issue 9 (3rd July 2013) - Kosaka, Ryo; Yada, Toru; Nishida, Masahiro; Maruyama, Osamu; Yamane, Takashi
Abstract A hydrodynamically levitated centrifugal blood pump with a semi‐open impeller has been developed for mechanical circulatory assistance. However, a narrow bearing gap has the potential to cause hemolysis. The purpose of the present study is to optimize the geometric configuration of the hydrodynamic step bearing in order to reduce hemolysis by expansion of the bearing gap. First, a numerical analysis of the step bearing, based on lubrication theory, was performed to determine the optimal design. Second, in order to assess the accuracy of the numerical analysis, the hydrodynamic forces calculated in the numerical analysis were compared with those obtained in an actual measurement test using impellers having step lengths of 0%, 33%, and 67% of the vane length. Finally, a bearing gap measurement test and a hemolysis test were performed. As a result, the numerical analysis revealed that the hydrodynamic force was the largest when the step length was approximately 70%. The hydrodynamic force calculated in the numerical analysis was approximately equivalent to that obtained in the measurement test. In the measurement test and the hemolysis test, the blood pump having a step length of 67% achieved the maximum bearing gap and reduced hemolysis, as compared with the pumps having step lengths of 0% and 33%. It was confirmed that the numerical analysis of the step bearing was effective, and the developed blood pump having a step length of approximately 70% was found to be a suitable configuration for the reduction of hemolysis.